Waste management, waste resource facilities and waste conversion processes - Demirbaş, Ayhan (ELSEVIER SCIENCE LTD, 2011)
In this study, waste management concept, waste management system, biomass and bio-waste resources, waste classification, and waste management methods have been reviewed. Waste management is the collection, transport, processing, recycling or disposal, and monitoring of waste materials. A typical waste management system comprises collection, transportation, pre-treatment, processing, and final abatement of residues. The waste management system consists of the whole set of activities related to handling, treating, disposing or recycling the waste materials. General classification of wastes is difficult. Some of the most common sources of wastes are as follows: domestic wastes, commercial wastes, ashes, animal wastes, biomedical wastes, construction wastes, industrial solid wastes, sewer, biodegradable wastes, non-biodegradable wastes, and hazardous wastes. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Waste management; Bio-waste; Waste classification; Waste management methods